Recent Advancements in Gremlin-1: Breast cancer - Nimrah Inam; Ayesha Hameed; Lubna Vohra; Sana Zeeshan (Journal of the Pakistan Medical Association, 2023)
One of the bone’s morphogenic protein (BMP) antagonists, Gremlin-1 or GREM-1, can bind directly to BMPs. GREM-1 can act in either BMP-dependent or -independent pathways, according to research. It reinforces organogenesis, tissue differentiation, and organ fibrosis. Recent research from numerous studies has demonstrated the significance of GREM-1 in the initiation, progression, and even metastasis of different cancers, including breast, cervical, gastric, and colorectal cancers. This review highlights the function of GREM-1 in the development of breast cancer and its effect on the cellular procedures and signalling pathways involved in carcinogenesis. Keywords: Bone Morphogenetic, Carcinogenesis, Organogenesis, Colorectal Neoplasms, breast cancers, stem cells